Differences in The Quality Of Feed on Blood Glucose Levels, Production and Quality Of Milk in Dairy Cattle - Leondro, Henny (Proceeding INTERNATIONAL SEMINAR IMPROVING TROPICAL ANIMAL PRODUCTION FOR FOOD SECURITY)
This study aims to determine the effect of different feed quality on blood glucose levels,production and quality of milk in dairy cattle. The material used in this study are 9 Friesian Holsteindairy cows with a weight range of 350-400 kg , lactation levels I-III , divided into 3 treatment groupsfeed are: T0 = 70% forage of corn + concentrate 30% (14% CP); T1 = Forage of Corn 60% + 40%concentrate ( 17% CP); T2 = Forage of Corn 50% + 50% concentrate (20% CP). This research methodused a Randomized Block Design. Data were analyzed by analysis of variance. The averageconsumption of dry matter T0, T1 and T2 respectively 11,95, 11,08 and 10,29 kg. The average bloodglucose concentration at T0, T1 and T2 respectively 53,00, 49,33 and 57,67 mg/dl. The averageproduction of milk at T0, T1 and T2 respectively was 13,60, 16,67 and 17,37 kg. The average fatlevels and fat content of milk on the T0, T1 and T2 respectively 4,8; 4,67; 3,68% and 0,65, 0,63 and0,64 kg. Average protein levels and protein content of milk on the T0, T1 and T2 respectively was3,56; 3,48; 3,45% and 0,48; 0,57 and 0,59kg. Average lactose levels and lactose content of milk onT0, T1 and T2 respectively was 4,85; 4,69; 4,58% and 0,60, 0,84 and 0,78kg.The conclusion from this study is the feeding with different quality (crude protein content of 14%,17% and 20%) did not significantly affect blood glucose levels, milk production and milk quality indairy cowsKey Words: Feed, Blood Glucose, Production Milk, Quality of Milk